What pulls ancestral tourists 'home'? An analysis of ancestral tourist motivations. (February 2018) - Murdy, Samantha; Alexander, Matthew; Bryce, Derek
Abstract: Ancestry has received limited attention within the tourism literature but is shown to play a crucial role in heritage tourism, especially for countries with extended diasporas such as Ireland, Italy India, China, and Scotland. The purpose of this study is to explore ancestral tourist motivations, and attain a broader understanding of this market. A survey of 282 ancestral tourists allowed the identification of three key factors: ancestral tourist motivation; heritage tourist motivations; and mass tourist motivation. These themes enabled a detailed analysis of clusters, identifying four ancestral segments: full heritage immersion; the ancestral enthusiast; general interest; and heritage focused. Given the lack of funding and resources currently available to ancestral tourism providers, the identification of these factors goes some way to highlighting productive areas of focus for promotional efforts and resources. Highlights: Three key ancestral motivations are identified: ancestral, heritage, and mass. Four ancestral tourist clusters identified using motivations. Personal ancestry is confirmed as the main reason of travel for ancestral tourists. However, without other elements there is a strong risk of under providing.